The effects of organization mission fulfillment and perceived organizational support on job performance The mediating role of work engagement - Karatepe, Osman M.; Aga, Mehmet (Emerald Group Publishing Ltd, 2016)
Purpose - Drawing from Bagozzi's (1992) reformulation of attitude theory, the purpose of this paper is to propose and test a conceptual model that links organization mission fulfillment (OMF) and perceived organizational support (POS) to job performance (JP) via work engagement (WE). Design/methodology/approach - Data gathered from frontline bank employees with a time lag of two weeks and their supervisors in Northern Cyprus were utilized to test the aforementioned relationships. Findings - The results from structural equation modeling suggest that OMF and POS foster WE. WE in turn stimulates employees' JP. In short, WE fully mediates the effects of OMF and POS on JP. Research limitations/implications - Incorporating creative performance into the conceptual model would shed further light on WE as a mediator of the effects of OMF and POS on various performance outcomes. Gathering data from frontline bank employees in similar islands would allow conducting a cross-national study. Practical implications - Management of banks can organize workshops where frontline employees can contribute to the preparation of the mission statement. Employees making such contribution will display elevated levels of WE, because they contribute to something which is significant and meaningful. Management should also use selective staffing procedures to hire individuals who are customer oriented and therefore feel energetic and dedicated and are engrossed in their work. Originality/value - This study contributes to the current knowledge base by linking OMF and POS to JP via WE in frontline service jobs in the retail banking industry.
Keywords: Internal marketing; Human resource management